The generation gap and its impact on the behavior of education studients - Pizarro Vásquez, Anahí Virginia (2024)
Currently, different generations are interacting in the academic environment: generation X, millennials (generation Y) and centennials (generation Z), the question arises as to whether there is a different perception of the importance of knowledge, skills, attitude and values ​​among students of different generations. To answer this question, this research was carried out with the objective of testing whether the level of importance regarding knowledge, skills, attitude and values ​​were different depending on the age of the education student at the Universidad Autónoma del Noreste (UANE) Monclova campus, Mexico. Individual interviews were applied on the university campus to a sample of 158 students who were studying careers related to education (undergraduate and postgraduate) at the Universidad Autónoma del Noreste, Monclova campus, Mexico. The analysis of the data obtained was carried out using the Kruskal-Wallis H statistical test to test the hypothesis. The results showed that the level of importance that each student perceives regarding knowledge, skills, attitude and values ​​is not different depending on their age range.